Histopathologic characteristics of therapy‐associated cutaneous neoplasms with vemurafenib, a selective BRAF kinase inhibitor, used in the treatment of melanoma. (29th April 2014) - Sufficool, Kari E.; Hepper, Donna M.; Linette, Gerald P.; Hurst, Eva A.; Lu, Dongsi; Lind, Anne C.; Cornelius, Lynn A.
Abstract : Background: Activating mutations in BRAF have been observed in up to 60% of melanomas, indicating a pivotal role for kinase deregulation in tumor progression. Vemurafenib is a specific inhibitor of BRAF for treatment of melanomas with activating BRAF V600E mutations and has been a major advancement in melanoma treatment. Treatment with vemurafenib, and to a lesser extent, sorafenib, a relatively non‐specific inhibitor of BRAF, has been associated with cutaneous squamous cell carcinoma (SCC). Methods: Clinical and microscopic characteristics of cutaneous neoplasms were evaluated following vemurafenib administration. Results: Twenty‐four of 47 (51%) patients receiving vemurafenib at our institution developed 146 total cutaneous neoplasms, with 75% developing multiple lesions. The median number of lesions in affected patients was three. Body distribution included head/neck (29%), chest/back (21%), upper (23%) and lower extremities (27%). Lesions were biopsied and pathologically showed multiple types of epidermal tumors including, but not limited to, verrucous keratoses with/without partial thickness dysplasia, actinic keratoses and well‐differentiated and invasive SCCs with/without keratoacanthomatous features. Conclusions: We describe the histopathologic findings of skin lesions potentially associated with vemurafenib. Additional investigation is necessary to further elucidate cutaneous neoplasms associated with vemurafenib; however, frequent dermatologic evaluation is warranted in all patients receiving BRAF inhibitors.